2006
DOI: 10.17660/actahortic.2006.718.22
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving in Greenhouses: Optimal Use of Climate Conditions and Crop Management

Abstract: In the last few years, energy consumption in greenhouses has gained increased interest, due to the liberalisation of the energy market and the increasing prices of natural gas. In this paper, the effects of a series of adaptations in greenhouse climate and cropping systems on crop production and energy consumption are presented. Greenhouse energy consumption is primarily determined by the temperature set points. Allowing temperatures to fluctuate, can conserve 3-13% energy, depending on the bandwidth applied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…However, acclimation of photosynthesis and production to high CO 2 concentration may occur (Besford et al, 1990;Peet et al, 1986). Dieleman et al (2006) found in current Dutch greenhouse systems, photosynthesis and production did not show adaptation to high CO 2 concentration.…”
Section: Productionmentioning
confidence: 68%
“…However, acclimation of photosynthesis and production to high CO 2 concentration may occur (Besford et al, 1990;Peet et al, 1986). Dieleman et al (2006) found in current Dutch greenhouse systems, photosynthesis and production did not show adaptation to high CO 2 concentration.…”
Section: Productionmentioning
confidence: 68%
“…Reducing energy consumption for heating has therefore become an important challenge. Many efforts have allowed the optimization of the daily average temperature and humidity as well as that of solar radiation and CO 2 concentration [4][5][6]. Furthermore, studies have proposed innovative strategies such as structural design, the use of energy-efficient covers, improved heating and ventilation systems, management of indoor micro-climates and use of renewable energy sources based on the location of greenhouses.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf photosynthetic rate is determined by the amount of photosynthetic protein per leaf area and CO 2 conductance in stomata [9]. In addition, a rise in the cover transmissivity allows not only to increase photosynthesis and production, but also to reduce the energy input in cold periods [10]. Under normal CO 2 concentrations and with adequate temperature conditions, photosynthetic activity is mainly affected by light intensity [11].…”
Section: Introductionmentioning
confidence: 99%